2005
DOI: 10.1096/fj.04-2437fje
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of acetaminophen: role of cyclo‐oxygenase

Abstract: Acetaminophen is one of the most commonly used drugs for the safe and effective treatment of pain and fever. Acetaminophen works by lowering cyclo-oxygenase products preferentially in the central nervous system, where oxidant stress is strictly limited. However, the precise mechanism of action for acetaminophen on cyclo-oxygenase activity is debated. Two theories prevail. First, it is suggested that acetaminophen selectively inhibits a distinct form of cyclo-oxygenase, cyclo-oxygenase-3. Second, it is suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
2
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 18 publications
2
82
2
5
Order By: Relevance
“…In fact, a previous investigation encouraged a reclassifi cation of COX inhibitors with regard to their ability to interfere with oxidation state of the enzyme and/or essential radicals in the reaction. The study showed that the COX-2 inhibitory effects of some inhibitors (naproxen, ibuprofen, rofecoxib) were signifi cantly blunted by increasing intracellular hydroperoxide levels, whereas the inhibitory effects of others (diclofenac, indomethacin) were essentially unaffected ( 65 ). Ongoing studies have to evaluate whether celecoxib may also infl uence other parameters involved in PG synthesis, such as cytosolic phospholipase A 2 , which has been demonstrated to be induced by high concentrations of celecoxib (50-200 µM) in Lewis lung carcinoma cells ( 41 ) but which appeared to be downregulated in a murine hepatoma cell line exposed to 200 and 400 µM celecoxib ( 66 ).…”
Section: Impact Of Exogenous Pgs On Nuclear and Total Levels Of Ppar ␥mentioning
confidence: 99%
“…In fact, a previous investigation encouraged a reclassifi cation of COX inhibitors with regard to their ability to interfere with oxidation state of the enzyme and/or essential radicals in the reaction. The study showed that the COX-2 inhibitory effects of some inhibitors (naproxen, ibuprofen, rofecoxib) were signifi cantly blunted by increasing intracellular hydroperoxide levels, whereas the inhibitory effects of others (diclofenac, indomethacin) were essentially unaffected ( 65 ). Ongoing studies have to evaluate whether celecoxib may also infl uence other parameters involved in PG synthesis, such as cytosolic phospholipase A 2 , which has been demonstrated to be induced by high concentrations of celecoxib (50-200 µM) in Lewis lung carcinoma cells ( 41 ) but which appeared to be downregulated in a murine hepatoma cell line exposed to 200 and 400 µM celecoxib ( 66 ).…”
Section: Impact Of Exogenous Pgs On Nuclear and Total Levels Of Ppar ␥mentioning
confidence: 99%
“…Others have hypothesized that paracetamol has no affinity for the active site of COXs, but instead blocks their activity by reducing the conversion of the active oxidized form of the enzymes to an inactive form; this would explain why paracetamol is more effective under reducing conditions of low peroxide concentration (32,127,155).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…1,2 Previous authors have suggested that paracetamol works by acting at the peroxidase segment of prostaglandin synthetase and inhibits activity. 3 To the best of our knowledge, our case is the first reported case of ductal closure associated with paracetamol outside of the newborn period. Further studies are needed to elucidate the role of paracetamol for ductal closure beyond the neonatal period.…”
mentioning
confidence: 65%